Sprachenpolitik und die Rolle der Fremdsprachen (Deutsch) in Südafrika - Von Maltzan, Carlotta (Stellenbosch Papers in Linguistics Plus, 2012)
Taking multilingualism in South Africa into account, this paper investigates language policy, language usage and the role of foreign languages, especially German, within the context of processes of transformation at universities since 1994, i.e. after the end of Apartheid. It is argued that foreign languages find themselves caught in the battle between ideology and practice and have to forge a new direction for themselves. Keywords: Schlüsselbegriffe: Sprachenpolitik, Südafrika, Rolle der Fremdsprachen, Deutsch, Universitäten in Südafrika, Bildung language policy, South Africa, role of foreign languages, German, South African universities, education